Pemanfaatan Media Sosial dalam Pelayanan Rerefensi 2.0 di Indonesia - Anwar, Ahmad (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
In today era, there is a change of paradigm in organizing library in which a library is supposed to provide Web 2.0. In fact, its kind of service is used only for a medium to inform and promote library in general. To optimilize its Web 2.0 within the library, it is therefore the library needs to think of library services innovation. Reference service as a part of library must be playing an important role to optimize its service, or in the other words, they might think innovatively. With the growing rapid of usage os sosial media, the service should be worked in online. There are many sosial media today. The current study is aimed to discover the implementation of Web 2.0 in Indonesia